Snowmass2021: letter of interest cosmology intertwined I : perspectives for the next decade - Valentino, Eleonora di; Anchordoqui, Luis A.; Akarsu, Özgür; Ali-Haimoud, Yacine; Amendola, Luca; Arendse, Nikki; Asgari, Marika; Ballardini, Mario; Basilakos, Spyros; Battistelli, Elia; Benetti, Micol; Birrer, Simon; et al. (Astroparticle physics, 2021)
The standard Λ Cold Dark Matter cosmological model provides an amazing description of a wide range of astrophysical and astronomical data. However, there are a few big open questions, that make the standard model look like a first-order approximation to a more realistic scenario that still needs to be fully understood. In this Letter of Interest we will list a few important goals that need to be addressed in the next decade, also taking into account the current discordances present between the different cosmological probes, as the Hubble constant H0 value, the σ8S8 tension, and the anomalies present in the Planck results. Finally, we will give an overview of upgraded experiments and next-generation space-missions and facilities on Earth that will be of crucial importance to address all these questions.